Respuesta :

Answer:

The sample loses [tex]\frac{1}{3}[/tex] of its mass every [tex]\frac{1}{3}[/tex] days.

Step-by-step explanation:

Expression that shows the relation between final mass of the element after 't' days is,

M(t) = [tex]900(\frac{8}{27})^t[/tex]

If M(t) = two third of the initial mass [After the loss of one third of the initial mass remaining mass of the element = 1 - [tex]\frac{1}{3}[/tex] = [tex]\frac{2}{3}[/tex]rd of the initial mass]

[tex]900\times \frac{2}{3}=900(\frac{8}{27})^t[/tex]

[tex]\frac{2}{3}=(\frac{8}{27})^t[/tex]

[tex]\frac{2}{3}=[(\frac{2}{3})^3]^t[/tex]

[tex](\frac{2}{3})^1=(\frac{2}{3})^{3t}[/tex]

By comparing powers on both the sides

3t = 1

t = [tex]\frac{1}{3}[/tex] day

Therefore, The sample loses [tex]\frac{1}{3}[/tex] of its mass every [tex]\frac{1}{3}[/tex] days.

ACCESS MORE